Environmental changes in the Vistula valley at Pleszów caused by Neolithic man - Wasylikowa, Krystyna; Starkel, Leszek; Niedziałkowska, Ewa; Skiba, Stefan; Stworzewicz, Ewa (Polska Akademia Nauk. Instytut Historii Kultury Materialnej, 1985)
Geomorphological, pedological, palaeobotanical and malacological studies were carried out in the edge zone of a loess terrace and the buried abandoned river channel situated at its foot. It has been found that this paleochannel was cut off before c. 4500 B. C. Local changes in the vegetation connected with the development of Early Neolithic settlement representing the Linear Pottery and Lengyel cultures have been reconstructed and the synchronousness of slope wash deposition with periods of intensive land cultivation has been discovered. The environmental conditions prevailing in the valley zone have been determined on the basis of the vegetation and malacofauna. The site at Pleszów indicates that as early as the Early Neolithic changes in the land use caused direct and prompt changes in plant communities and soil degradation
ill. ; 29 cm
Annex: W. G. Mook, Comments to radiocarbon dates from the site Pleszów in Cracow
Keywords: Neolithic -- Poland; environment; paleobotany; palinology; plant remains; molluscs remains; environmental changes; environment and settlement; radiocarbon dating; Pleszów (Poland)